THE DEVELOPMENT OF MANAGEMENT SYSTEM FOR LADPRAO CANAL COOPERATIVES COMMUNITY FUND - นาคลังกา กัลยา; รองทอง ณัฐกานต์; สังฆมาศ คฑาวุฒิ; โถสุวรรณจินดา วงศ์วิภา; โฆษิตพิพัฒน์ อรอนงค์; วิริยะวิทย์ ณัฐนันท์; จันทร์ควง พัฒนพงษ์ (Academic Journal Phranakhon Rajabhat University, 2018)
This research aimed to determine the development of management system for Ladprao Canal cooperatives community fund. Mixed Methods Research was used as the research methodology. For quantitative research, data were collected by distributing the questionnaires to participating in cooperatives community fund. For qualitative research, data were collected from participating in cooperatives community fund by Participation Action Research (PAR) through workshops and sharing lessons learned with 21 Ladprao Canal cooperatives community fund to supplement the quantitative analysis. Based on quantitative and qualitative analysis, the causing problem and management approach of the cooperative is based on 4M principles include 1) Man found that a lack of staff and understanding of Cooperative ideology. This is to cooperatives community fund should provide more training by using Knowledge Management method. 2) Money found that the budget is not enough. This is leads to cooperatives community fund should provide more investment to creative business. 3) Management found that information system is the key success to control in cooperatives community fund such as lists of members and other database. and 4) Material found that The location and materials of office equipment are not enough. So, cooperatives community fund should provide convenience technology for all participate to work with efficiency. Furthermore, these guidelines will lead to empowerment and cumulative idea to work on cooperatives community fund.